2015
DOI: 10.1017/jsl.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Pebble Games and Linear Equations

Abstract: We give a new, simplified and detailed account of the correspondence between levels of the Sherali-Adams relaxation of graph isomorphism and levels of pebble-game equivalence with counting (higher-dimensional Weisfeiler-Lehman colour refinement). The correspondence between basic colour refinement and fractional isomorphism, due to Tinhofer [22,23] and Ramana, Scheinerman and Ullman [17], is re-interpreted as the base level of Sherali-Adams and generalised to higher levels in this sense by Atserias and Maneva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…LP hierarchies and FPC. Another intriguing connection between counting logics and linear programming is established in [Atserias and Maneva 2012;Grohe and Otto 2012] where it is shown that the hierarchy of Sherali-Adams relaxations [Sherali and Adams 1990] of the graph isomorphism integer program interleaves with equivalence in k-variable logic with counting (C k ). It is suggested [Atserias and Maneva 2012] that inexpressibility results for C k could be used to derive integrality gaps for such relaxations.…”
Section: Resultsmentioning
confidence: 99%
“…LP hierarchies and FPC. Another intriguing connection between counting logics and linear programming is established in [Atserias and Maneva 2012;Grohe and Otto 2012] where it is shown that the hierarchy of Sherali-Adams relaxations [Sherali and Adams 1990] of the graph isomorphism integer program interleaves with equivalence in k-variable logic with counting (C k ). It is suggested [Atserias and Maneva 2012] that inexpressibility results for C k could be used to derive integrality gaps for such relaxations.…”
Section: Resultsmentioning
confidence: 99%
“…The following lemma is, at least implicitly, from [15]. As the formal framework is different there, we nevertheless give a proof.…”
Section: Lemma 42mentioning
confidence: 97%
“…Complementing recent research on linear and semidefinite programming approaches to GI [1,10,15,19,20], we investigate the power of GI-algorithms based on algebraic reasoning techniques like Gröbner basis computation. The idea of all these approaches is to encode isomorphisms between two graphs as solutions to a system of equations and possibly inequalities and then try to solve this system or relaxations of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The GRAPHISOMORPHISM problem can be thought of as kind of constraint satisfaction problem (CSP), and readers familiar with LP/SDP hierarchies for CSPs might see an analogy between k-dimensional WL and level-k LP/SDP relaxations. A very interesting recent work of Atserias and Maneva [AM13] (see also [GO12]) shows that this is more than just an analogy -it shows that the power of WL k is precisely sandwiched between that of the kth and (k+1)st level of the canonical Sherali-Adams LP hierarchy [SA90]. (In fact, it had long been known [RSU94] that WL 1 is equivalent in power to the basic LP relaxation of GISO.)…”
mentioning
confidence: 99%